Adaptive Governance of Purwodadi Village Malang in Handling COVID-19 - Garnis Saraswati Dewi; Yana Syafriyana Hijri (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
This paper aims to examine how the local government responds to the central government’s policies and local governments in handling Covid-19 in Purwodadi Village. The government's involvement, at the local level, which covers adaptability, institutional strategies, and political strategies is part of the accomplishment in handling Covid-19, especially in Malang City. This research utilized a qualitative descriptive method with a case study approach to determine adaptive governance in Purwodadi village. Moreover, the data were gained from primary data and secondary data. Likewise, data collection was done through observation, interviews, and documentation. The result of this research revealed that institutionally, Purwodadi Village Government implemented central and local government policies as its adaptability through strategic steps with a collaborative framework among stakeholders; Indonesian Military (TNI), National Police (Polri), Air Patrol, and the community. Purwodadi village collaboratively handled COVID-19 by strengthening health protocols and limiting the community activities. Additionally, door-to-door Covid-19 dissemination to the public was done by strengthening the role of neighborhoods unit and community units (RT and RW), implementing a massive campaign about health care that involved communities such as Pemuda Pancasila and the Indonesian Youth National Community.